Effects of smoking on agricultural productivity - Haque, Samiul; Abedin, Naveen; Fakir, Adnan M. S.; Hannan, Rafe; Alam, Rafa (Agricultural and Applied Economics Association, 2019)
Objective: We estimate the effect of primary farmer’s smoking status on the productivity of family labor working in the household’s main agricultural land; Agricultural productivity is measured by value addition per acre, which is the value of output per acre minus the costs of variable non-labor direct inputs (seeds, fertilizers and pesticides) per acre; The primary farmer is the lead decision-maker of allocation of resources for production.